Venom: lethal protector ii (2023) ebook Life and deaths. - Michelinie, David (Venom: Lethal Protector II (2023), 2024)
Collects Venom: Lethal Protector II (2023) #1-5. Venom vs. Doctor Doom! Venom co-creator David Michelinie returns with a new story set in the sinister symbiote's past, back when brains - and Spider-Man - were still on the menu! Prepare for an epic that will take Venom far from the streets of NYC - all the way to the kingdom of Latveria! When Silver Sable and S.H.I.E.L.D. come calling, Venom is recruited into a battle to stop a tech-worshipping cult from getting their hands on a doomsday weapon. Speaking of doom, there's a certain supreme leader of Latveria who also has his titanium-armored eyes on the same prize - and he's not the only one! Brock is about to be challenged like never before! What (or who) will Venom need to overcome the fiercest foe in the Marvel Universe?